Xenicola brauni sp. n., a new katydid species (Orthoptera: Tettigoniidae: Phaneropterinae) from the Atlantic Forest, southeastern Brazil - Fianco, Marcos; Engelking, Phillip Watzke [UNESP]; Faria, Luiz R. R. (Magnolia Press, 2020)
A new species of Xenicola Uvarov, 1940 (Orthoptera: Tettigoniidae: Phaneropterinae), X. brauni sp. n., is described from the Atlantic Forest of southeastern Brazil. Morphological comparisons with all other known species of Xenicola are presented and discussed. This is the first record of Xenicola in southeastern Brazil, and is also the northernmost record of the genus within the Brazilian Atlantic Forest.
Keywords: Anisophya; Bertioga; micropterous; Odonturini; taxonomy